Hydrogeochemical processes governing the origin, transport and fate of major and trace elements from mine wastes and mineralized rock to surface waters - Nordstrom, D. Kirk (Applied geochemistry, 2011)
► Hydrogeochemistry of mines and mineralized areas is complex. ► Mass balances and saturation indices add insight and organization to acid rock drainage data. ► Large database confirms geochemical generalizations for behavior of iron and aluminum. The formation of acid mine drainage from metals extraction or natural acid rock drainage and its mixing with surface waters is a complex process that depends on petrology and mineralogy, structural geology, geomorphology, surface-water hydrology, hydrogeology, climatology, microbiology, chemistry, and mining and mineral processing history. The concentrations of metals, metalloids, acidity, alkalinity, Cl −, F − and SO 4 2 - found in receiving streams, rivers, and lakes are affected by all of these factors and their interactions. Remediation of mine sites is an engineering concern but to design a remediation plan without understanding the hydrogeochemical processes of contaminant mobilization can lead to ineffective and excessively costly remediation. Furthermore, remediation needs a goal commensurate with natural background conditions rather than water-quality standards that might bear little relation to conditions of a highly mineralized terrain. This paper reviews hydrogeochemical generalizations, primarily from US Geological Survey research, that enhance our understanding of the origin, transport, and fate of contaminants released from mined and mineralized areas. Mobility of potential or actual contaminants from mining and mineral processing activities depends on (1) occurrence : is the mineral source of the contaminant actually present? (2) abundance : is the mineral present in sufficient quantity to make a difference? (3) reactivity : what are the energetics, rates, and mechanisms of sorption and mineral dissolution and precipitation relative to the flow rate of the water? and (4) hydrology : what are the main flow paths for contaminated water? Estimates of relative proportions of minerals dissolved and precipitated can be made with mass-balance calculations if minerals and water compositions along a flow path are known. Combined with discharge, these mass-balance estimates quantify the actual weathering rate of pyrite mineralization in the environment and compare reasonably well with laboratory rates of pyrite oxidation except when large quantities of soluble salts and evaporated mine waters have accumulated underground. Quantitative mineralogy with trace-element compositions can substantially improve the identification of source minerals for specific trace elements through mass balances. Post-dissolution sorption and precipitation (attenuation) reactions depend on the chemical behavior of each element, solution composition and pH, aqueous speciation, temperature, and contact-time with mineral surfaces. For example, little metal attenuation occurs in waters of low pH (<3.5) and metals tend to maintain element ratios indicative of the main mineral or group of minerals from which they dissolved, except Fe, SiO 2, and redox-sensitive oxyanions (As, Sb, Se, Mo, Cr, V). Once dissolved, metal and metalloid concentrations are strongly affected by redox conditions and pH. Iron is the most reactive because it is rapidly oxidized by bacteria and archaea and Fe(III) hydrolyzes and precipitates at low pH (1–3) which is related directly to its first hydrolysis constant, pK 1 = 2.2. Several insoluble sulfate minerals precipitate at low pH including anglesite, barite, jarosite, alunite and basaluminite. Aluminum hydrolyzes near pH 5 (pK 1 = 5.0) and provides buffering and removal of Al by mineral precipitation from pH 4–5.5. Dissolved sulfate behaves conservatively because the amount removed from solution by precipitation is usually too small relative to the high concentrations in the water column and relative to the flow rate of the water.